Microbiology of food and animal feeding stuffs. Preparation of test samples, initial suspension and decimal dilutions for microbiological examination. General rules for the preparation of the initial suspension and decimal dilutions Part 1, (15th May 1999) - British Standards Institution,
No abstract available